2012
DOI: 10.1371/journal.pone.0036891
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Repression of RARRES1 Is Mediated by Methylation of a Proximal Promoter and a Loss of CTCF Binding

Abstract: BackgroundThe cis-acting promoter element responsible for epigenetic silencing of retinoic acid receptor responder 1 (RARRES1) by methylation is unclear. Likewise, how aberrant methylation interplays effectors and thus affects breast neoplastic features remains largely unknown.Methodology/Principal FindingsWe first compared methylation occurring at the sequences (−664∼+420) flanking the RARRES1 promoter in primary breast carcinomas to that in adjacent benign tissues. Surprisingly, tumor cores displayed signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…In validation of the importance of methylation of the promoter region of RARRES1, we performed 5-methylcytosine (5-mC) ChIP on RARRES1-silenced Hs578T cells using 4 locations ranging from ~1000bp upstream of the transcription start site (TSS) to within 100bp of the TSS (as described in Peng, 2012 [17], indicated in Figure 6B as A-D). We observed a decrease in 5-mC following decitabine treatment which was most pronounced in Region C and D (Figure 7B), which is located nearest to site 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In validation of the importance of methylation of the promoter region of RARRES1, we performed 5-methylcytosine (5-mC) ChIP on RARRES1-silenced Hs578T cells using 4 locations ranging from ~1000bp upstream of the transcription start site (TSS) to within 100bp of the TSS (as described in Peng, 2012 [17], indicated in Figure 6B as A-D). We observed a decrease in 5-mC following decitabine treatment which was most pronounced in Region C and D (Figure 7B), which is located nearest to site 1.…”
Section: Resultsmentioning
confidence: 99%
“…Our own work identified the cancer stem cell marker and retinoic-acid (RA) producing enzyme, aldehyde dehydrogenase 1A3 (ALDH1A3), as promoting or suppressing tumor growth in a context-dependent manner in TNBC [15]. The RA receptor responder protein 1 (RARRES1) has also been identified as either suppressing or promoting tumor growth, depending on the study [16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous candidate gene studies investigated promoter hypermethylation of breast cancer lesions and identified aberrant methylation at the promoters of RASSF1A, Hin-1, RAR-b, Cyclin D2, twist, GSTP1, ABCB1, FOXC1, MGMT, MLH1, PPP2R2B, PTEN, BRCA2, CDH13, MSH6 and RARRES1, and others [8][9][10][11][12]. Identification of these genes has helped begin to elucidate the molecular pathogenesis of breast carcinoma, as it reveals intracellular pathways that are altered that likely contribute to oncogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…CTCF was also recognized as a potential tumor suppressor gene in breast cancer (Filippova et al, 1998(Filippova et al, , 2002Rasko et al, 2001;Fiorentino and Giordano, 2012), and CTCF suppresses breast cancer growth (Tiffen et al, 2013). To our knowledge, all publications currently available mainly describe that loss of CTCF binding due to hypermethylation leads to subsequent silencing of tumor suppressor gene loci, including BRCA1 (Butcher et al, 2004), retinoblastoma (Rb) (De la Rosa-Velazquez et al, 2007), p16(INK4a) (Witcher andEmerson, 2009), p53 (Soto-Reyes andRecillas-Targa, 2010), and retinoic acid receptor responder 1 (RARRES1) (Peng et al, 2012). In our study, none of the invasive breast cancer and DCIS samples was methylated at the CTCF promoters examined, although we have used the commonly studied promoter/upstream by 500 bases and 5¢ UTR exons region with CpG island(s).…”
Section: Discussionmentioning
confidence: 99%
“…Previous candidate gene studies investigated promoter hypermethylation of breast cancer lesions and identified aberrant methylation at the promoters of RASSF1A, Hin-1, RAR-b, Cyclin D2, twist, GSTP1, ABCB1, FOXC1, MGMT, MLH1, PPP2R2B, PTEN, BRCA2, CDH13, MSH6, RARRES1, SLIT2, and WIF1 and others (Fackler et al, 2003;Lee, 2007;Muggerud et al, 2010;Moelans et al, 2011;Peng et al, 2012;Alvarez et al, 2013). Identification of these genes has helped begin to elucidate the molecular pathogenesis of breast carcinoma, as it reveals intracellular pathways that are altered that likely contribute to oncogenesis.…”
mentioning
confidence: 99%